Ferrite as an efficient microwave absorber - Yadav R.; Agrawal M.; Panwar R. (My University, 2025)
Microwave technology progression from lower to higher frequencies along with required bandwidths is an open topic for research. Nonconducting microwave materials are commonly needed to fill the technological variances. Ferrites merge the characteristics of an electrical insulator with those of a magnetic material. These dual characteristics tend to ferrites as a potential contender in improving microwave technology. Its simplicity in preparation and extraordinary flexibility in adjusting its magnetic characteristics has sparked more research into it. On the other hand, efficient microwave absorbing materials (MAMs) are always needed for suppressing electromagnetic (EM) waves for both commercial and defense applications. Therefore, developing an effective MAM to achieve EM wave trapping and absorption from lower to higher frequencies with wider absorption bandwidth requires the development of innovative materials and structures. This chapter presents in-depth research on current efforts to develop ferrite material properties and the structures made from their composites that are used for absorbing microwave radiation. Various ferrite-based MAMs are compared with the relevant microwave absorption principle. © 2023 Nova Science Publishers, Inc.